The Influence of Using Documentary Films on Students’ Writing Ability of Explanation Text - Murniasih Murniasih; Melia Najihatul Ummah (Jurnal Indonesia Sosial Sains, 2024)
This research aims to obtain empirical evidence of the influence of using Documentary Films on students’ writing ability of explanation text. The method of this research was a quantitative method using a quasi-experimental design. The population of this research was the eleventh-grade students at one of the private schools in Tangerang Selatan in the academic year 2019/2020 with 61 pupils in total. The sample of this study was selected by purposive sampling technique and was divided into two classes; experimental class and control class. In collecting data from both classes, the researcher used a written test as an instrument. Moreover, the data from both the pre-test and post-test were analyzed by using a t-test with IBM SPSS 20. The result indicated that the post-test mean score of the experimental class was higher than the post-test mean score of the control class, 76.97 > 67.16. Then the sig. 2-tailed (ρ) was lower than the alpha, 0.000 < 0.05. It proved that H0 was rejected and Ha was accepted. Therefore, the effect size calculation result showed 1.60, which means it is at a strong level. Therefore, it proved that there was a significant influence of using documentary films on students’ writing ability of explanation text.